Evaluation of compliant handle for endosurgical grasper using pseudo-rigid-body method / Solehuddin Shuib, M. Ikhwan Zaini Ridzwan and M. N. Mohd. Ibrahim - Shuib, Solehuddin; Ridzwan, M. Ikhwan Zaini; Mohd. Ibrahim, M. N. (UPENA, 2006)
The endosurgical grasper is a tool used for tissue manipulation in an endoscopic surgery. By adding a controller into the device, a surgeon can control both the grasping and the input forces.